Metode Hermeneutik dalam Pendidikan - Sembodo Ardi Widodo (Unisia, 2008)
Hermeneutics is an art of interpretation or a philosophical study of understanding. It has widerrange of understanding; not only canonical texts, but also all texts, from teaching manuals toliterary classics. Human acts and products, such as the act of teaching and the institution ofschool or university are interpreted. Here, we can see that the formulation of vision, mission,and the goal of any school and university is a result of interpretation or dialogue. Not only in thiseducational aspect hermeneutics plays its role, but also in teaching-learning aspect. Accordingto hermeneutics, teaching is an art, not a science or technology. Teaching-learning processis like a dialogue or game in which participants are carried by something larger than themselvestoward an insight they have not anticipated. Dialogue presupposes a subject and adesire to understand it. Openness on both sides is essential. No one must come with his mindmade up. In a give and take, each participant arrives at a new understanding. Finally, genuinedialogue makes fusion of each participant’s mental horizon.Keywords: hermeneutics, interpretation, philosophy, understanding, education.